A Novel Personalized Nutrition Program Improves Health and Lifestyle Behaviors: Subgroup Analysis Results from Habit's Personalized Approaches to Health (PATH) Study (P15-019-19) - Winters, Barbara (Curr Dev Nutr, 2019)
OBJECTIVES: This study evaluates the impact of a digitally-delivered systems biology-based personalized nutrition (PN) program (Habit LLC, Oakland, CA), that included nutrition and behavior advice, and meals. METHODS: In this single-arm, multi-phase, open-label study (clinicaltrials.gov: NCT03424395), participants (n = 107; 67% female) were provided a Fitbit® Activity Tracker and completed an at-home kit that included collection of DNA and capillary blood before and after (30 and 120 min) consuming a mixed macronutrient challenge beverage. Participants completed a 10-week run-in and 10-week PN program intervention phase. The intervention included personalized nutrition and behavior advice and meals (2 meals/day; 5 days/week) tailored to dietary subgroups. Here we report on changes in diet, anthropometrics, and biomarkers of two subgroups (Range Seekers [RS] and Protein Seekers [PS]) that differed in anthropometrics and biological measures at baseline and were provided different dietary recommendations. RESULTS: At baseline, there were no differences between groups in nutrients assessed, however, compared to RS (n = 48), PS (n = 22) had higher BMI, weight, body fat %, waist and hip circumference (all P < 0.0001), HOMA-IR, age, (both P < 0.01), muscle mass, diastolic blood pressure, hepatic insulin resistance index and c-peptide (all P < 0.05). After the intervention, both groups reduced intakes of calories (P < 0.001) and % calories from saturated fat and monounsaturated fat (both P < 0.05). Intakes of total fat, saturated fat, and sodium (all P < 0.001) as well as carbohydrate and total sugars (both P < 0.05) were also reduced. RS and PS increased vitamin C and fiber intakes (P < 0.001). PS, but not RS, received advice to increase protein intake, accordingly % calories from protein increased in PS by 28% (P < 0.001). PS also increased intake of b-carotene and vitamin A (P < 0.01). BMI and weight decreased in both groups (P < 0.001) after the intervention, with greater extent of weight loss observed in PS. In addition to weight loss in PS, a reduction in total and LDL cholesterol (P < 0.001) was observed. CONCLUSIONS: Together, these results support the efficacy of a digitally-delivered PN program, differentiated by subtype, in improving dietary patterns and health indicators. FUNDING SOURCES: Habit, LLC.